Citizen Science to Investigate the Ecophysiological Responses of Mediterranean Shrubland Vegetation in an Urban Open-Air Laboratory - Valerio Lazzeri; Francesca Bretzel; Graziella Rossini; Laura Pellegrino; Laura Marchetti; Rosella Panti; Enrica Talà; Antonio Martelli; Andrea Scartazza (Land)
Urban biodiversity is essential for enhancing liveability for both humans and wildlife by providing a range of ecosystem services. Therefore, it is crucial to raise awareness among citizens, particularly schoolchildren, about the significance of biodiversity in urban environments. To this end, an Open-Air Laboratory was established in an urban park of an Italian Mediterranean city (Livorno), where natural vegetation flourishes. This initiative engaged schoolchildren in experimental campaigns to collect ecophysiological data on local wild woody species. Specifically, the students were tasked with identifying various wild woody species and, under the guidance of researchers, recording specific leaf ecophysiological traits, such as leaf mass per area, leaf pigments, and chlorophyll fluorescence. The results, which highlighted seasonal variations in leaf ecophysiological traits and interspecific differences, were analysed in relation to the environmental conditions documented by the schoolchildren. This analysis revealed distinct plant strategies for coping with winter and summer stressful periods. The methodology employed in this project, which involved schoolchildren in research activities, not only fostered environmental awareness among young participants but also serves as a pilot model for public engagement in scientific research.